1995
DOI: 10.1038/nm0795-654
|View full text |Cite
|
Sign up to set email alerts
|

Altered striatal dopamine re-uptake site densities in habitually violent and non-violent alcoholics

Abstract: Animal studies suggest that development of substance dependence is associated with dopaminergic activity in striatum and the limbic system. Several genetic studies indicate that allele A1 is associated with both D2 receptor density and alcoholism, although these findings have remained controversial. We studied striatal dopamine (DA) re-uptake site densities in 48 subjects (19 healthy controls, 19 habitually impulsive violent alcoholics, and 10 non-violent alcoholics) with single photon emission computed tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
97
1
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(102 citation statements)
references
References 27 publications
3
97
1
1
Order By: Relevance
“…20 Recently we observed that the striatal dopamine re-uptake site densities are markedly lower among non-violent alcoholics than in healthy controls while habitually violent alcoholics (reminiscent of Cloninger type 2) 19 have slightly higher DA transporter densities than con- trols. 21 These findings on D 2 receptors and DA transporters have been regarded as the first identification of a specific neuroregulatory deficit in type 1 alcoholism. 22 Results of a recent PET study on alcoholics showed lower D 2 -receptor density, but DA transporter densities were not decreased among five alcoholic patients with a mean alcoholism onset age of 19 years (implying that many of these subjects were possibly type 2 rather than type 1 alcoholics).…”
Section: Introductionmentioning
confidence: 92%
“…20 Recently we observed that the striatal dopamine re-uptake site densities are markedly lower among non-violent alcoholics than in healthy controls while habitually violent alcoholics (reminiscent of Cloninger type 2) 19 have slightly higher DA transporter densities than con- trols. 21 These findings on D 2 receptors and DA transporters have been regarded as the first identification of a specific neuroregulatory deficit in type 1 alcoholism. 22 Results of a recent PET study on alcoholics showed lower D 2 -receptor density, but DA transporter densities were not decreased among five alcoholic patients with a mean alcoholism onset age of 19 years (implying that many of these subjects were possibly type 2 rather than type 1 alcoholics).…”
Section: Introductionmentioning
confidence: 92%
“…This is in contrast to the observed serotonergic deficit in early-onset type 2 alcoholism, which is characterized by novelty seeking, impulsive behavior and social hostility. 9 Preliminary results from positron emission tomographic (PET) and single photon emission tomographic (SPET) studies have indicated alterations in either dopamine transporter (DAT) densities or presynaptic DA function in the striatum of type 1 alcoholics [10][11][12] and in unclassified (type 1 vs type 2) alcoholics, 13 although contradictory results have also been reported in a study of unclassified alcoholics. 14 Other articles have reported low DA D 2 receptor densities in the striatum of unclassified alcoholics [14][15][16] and endocrinological measurements have shown decreased DA mediated activity among unclassified alcoholics.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using single photon emission computed tomography revealed that the highest concentrations of DAT1 are found in the basal ganglia, and striatal density was shown to be markedly lower in non-violent alcoholics. 11 The 40-bp variable number of tandem repeats (VNTR) polymorphism was found in the 3Ј-untranslated region of the DAT1 gene. 11,12 Several groups reported the association of the VNTR-polymorphism in the 3Ј-untranslated region of the DAT1 gene and alcoholism with low activity of aldehyde dehydrogenase II, 13 and with alcohol withdrawal seizures or delirium.…”
Section: Introductionmentioning
confidence: 99%
“…11 The 40-bp variable number of tandem repeats (VNTR) polymorphism was found in the 3Ј-untranslated region of the DAT1 gene. 11,12 Several groups reported the association of the VNTR-polymorphism in the 3Ј-untranslated region of the DAT1 gene and alcoholism with low activity of aldehyde dehydrogenase II, 13 and with alcohol withdrawal seizures or delirium. 14 The linkage and association studies between the VNTR polymorphism and schizophrenic disorders have been performed, but the relationship between the DAT1 gene and these disorders is still unclear.…”
Section: Introductionmentioning
confidence: 99%